Waste handling practices in the healthcare industry (New Jersey : Industrial Training Systems Corporation, 1988)
Identify the five major waste streams ; chemical waste streams, infectious waste streams, pharmaceutical waste streams, radioactive waste streams and routine or general waste
Video is accompanied by 1 leader's guide
Keywords: Factory and trade waste -- Management; Refuse and refuse disposal; Radioactive waste disposal